2021
DOI: 10.3389/fonc.2021.645370
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: RAB10-ALK: A Novel ALK Fusion in a Patient With Gastric Cancer

Abstract: Gastric cancer is one of the most common cancers, while the current treatment options for gastric cancer are relatively scarce due to insufficient understanding of molecular characteristics and subtypes of gastric cancer. Different gene rearrangements of anaplastic lymphocyte kinase (ALK) have been reported in several types of cancer, especially in NSCLC. The first-generation ALK tyrosine kinase inhibitor (TKI) crizotinib, second-generation (ceritinib, alectinib, and brigatinib) and third-generation (lorlatini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Nonetheless, both studies demonstrated the rarity of ALK positivity in gastric cancer. Recently, a novel RAB10-ALK fusion was reported in a Chinese patient with gastric cancer, 12 and this is the second and third case report of ALK fusion in gastric cancer.…”
Section: Discussionmentioning
confidence: 79%
“…Nonetheless, both studies demonstrated the rarity of ALK positivity in gastric cancer. Recently, a novel RAB10-ALK fusion was reported in a Chinese patient with gastric cancer, 12 and this is the second and third case report of ALK fusion in gastric cancer.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, a novel form of ALK gene fusion was identified, being the first gastric adenocarcinoma case with RAB10-ALK fusion [40]. On the contrary, another study did not find ALK fusions by FISH and gene sequencing methods in gastric adenocarcinoma [41].…”
Section: Discussionmentioning
confidence: 98%
“…Some other targets also showed promising clinical results in advanced GC, such as fibroblast growth factor receptor 2 ( FGFR2 ) amplification [ 167 ], epidermal growth factor receptor ( EGFR ) amplification [ 168 ], MET amplification [ 169 ], and alterations of homologous recombination deficiency–related genes [ 170 ]. In addition, there are very rare (prevalence <1%) targetable tissue–agnostic variants [ 171 ] such as BRAF V600E [ 172 ], anaplastic lymphoma kinase ( ALK ) fusion [ 173 ], and reactive oxygen species 1 ( ROS1 ) fusion [ 174 ].…”
Section: Application Of Standard Pathology Reportmentioning
confidence: 99%